2011
DOI: 10.1002/ptr.3259
|View full text |Cite
|
Sign up to set email alerts
|

Liquiritigenin induces mitochondria‐mediated apoptosis via cytochrome c release and caspases activation in heLa Cells

Abstract: It has been demonstrated that many flavonoids possess a potent and broad spectrum of antitumor activity. Liquiritigenin is a flavanone extracted from Glycyrrhizae. This study investigated the effects of liquiritigenin on cell viability and apoptosis induction in human cervical carcinoma (HeLa) cells. The results show that liquiritigenin significantly suppressed cell proliferation in a dose- and time-dependent manner in HeLa cells. In addition, liquiritigenin promoted apoptosis in HeLa cells, evidenced by apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 37 publications
2
31
0
Order By: Relevance
“…While our previous studies have demonstrated the effects of PGD in alleviating hyperPRL in patients and animal model,this further showed that, as a major bioactive components of PGD, LQ is significantly effective in inhibiting pituitary tumour growth; this antitumour effect appears to be associated with its induction of apoptotic death via Ras/ERKs and ROS‐dependent mitochondria pathways. These results are consistent with previous findings of LQ in various human tumour cells …”
Section: Discussionsupporting
confidence: 94%
“…While our previous studies have demonstrated the effects of PGD in alleviating hyperPRL in patients and animal model,this further showed that, as a major bioactive components of PGD, LQ is significantly effective in inhibiting pituitary tumour growth; this antitumour effect appears to be associated with its induction of apoptotic death via Ras/ERKs and ROS‐dependent mitochondria pathways. These results are consistent with previous findings of LQ in various human tumour cells …”
Section: Discussionsupporting
confidence: 94%
“…Data from our group and others have already demonstrated the cytotoxic effects of LQ in pituitary adenoma cells, Hela cells [30], SMMC-7721 cells [10], human lung fibroblasts, and peripheral lymphocytes [9]. In our present study, the potential antitumor effect on hepatocellular carcinoma was investigated in in vitro and in vivo models.…”
Section: Discussionmentioning
confidence: 67%
“…Cells (2 × 10 5 cells/well) were harvested after treatment with 0.3 μg/mL of Epi and/or 25 μM of 8HD for 48 h. Fifty microlitres of the cell suspension was then mixed with 50 μL of caspase-3, -8, and -9 reagents containing the corresponding luminogenic substrate of Ac-DEVD-pNA, Ac-LETD-pNA, and Ac-LEHD-pNA, respectively, at room temperature for 30 min. Released aminoluciferin luminescence levels were detected using a luminometer (MiniLumat LB9506; Berthold, Bad Wildbad, Germany) [48]. …”
Section: Methodsmentioning
confidence: 99%